Painéis para tratamento acústico utilizando fibras naturais - Campos, Rubya Vieira de Mello (2012)
The large amount of solid waste, especially organic waste, has excellent potential for development of new materials, thus reducing their disposal in landfills. This study shows the potential use of fibrous residues, which can be transformed into low cost products and quality suitable for construction. Justified the development of this study depending on the amount of waste produced at the national level and also considering that they are an important source of fibrous raw material, indicating potential with respect to the acoustic treatment. The aim of this study was to develop panels for acoustic treatment that provide favorable results to the control of noise indoors. The absorber panels were fabricated in the Laboratory of Applied Chemistry, State University of Paraná (UNESPAR) - Campus de Campo Mourão / FECILCAM. For producing the same, different materials were used, such as organic waste water, calcium oxide, cassava starch, dolomite and gypsum, among others. Was determined by impedance tube sound absorption curve of the fiber boards of cassava. Preliminary results obtained in cassava panels fiber had low quality sound absorption according to the characteristics of porosity and binder used for making the same. New fibers with different binders were tested and showed better results, among them the fibers of oats and cane sugar. Mechanical, biological and acoustic panels with fibers of cane sugar and oats were performed. The results were satisfactory and can be thought of panels used in the form of panels resonating/vibrating, being necessary to prove the efficiency with new tests.